Basic education for human development: a programme for expansion of Non-Formal Primary Education (NFPE), 1993-1995 - BRAC (© BRAC, 2016)
1. Introduction 2. NFPE programme 3. The Bangladesh background: Primary education, Enrollment and dropouts, Government plans and programme, External support for primary education 4. The impact of the prevailing situation 5. The solution 6. Proposal for the opening of 35,500 Non-formal primary schools-1993-1995.